Pengaruh Tingkat Pengangguran Terbuka dan Inflasi Terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Parlin Damanik; Darwin Damanik (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study analyzes the effect of open unemployment rate and inflation on economic growth in Jambi Province. Data from 2007 to 2021 was used and panel regression analysis method was used. The results show that the open unemployment rate and inflation have a significant negative effect on economic growth. These findings emphasize the importance of reducing unemployment and controlling inflation to promote better economic growth in Jambi Province.